Modelling continuance intention in mobile commerce usage activities: An early insight - Azyanee Luqman; Razli Che Razak; Mohammad Ismail; Mohd Afifie Mohd Alwi (TextRoad Publication, 2016)
This article, which is based on a preliminary study, aims to examine Malaysian consumers’ continuance intention in mobile commerce usage activities by extending the Expectation-Confirmation Model (ECM). Data was gathered from 45 consumers who had prior experience using mobile commerce and analyzed using Partial Least Squares structural equation modelling (PLS-SEM) technique. Findings revealed that only satisfaction was found to be significantly related to continuance intention, explaining 68.6% of the variance. Surprisingly, perceived usefulness and personal innovativeness were found to have no significant relationships with continuance intention. Finally, limitation and suggestions for future research are also elaborated.